Secondary Complement Deficiency Impairs Anti-Microbial Immunity to Klebsiella pneumoniae and Staphylococcus aureus During Severe Acute COVID-19 - Ali, Youssif M.; Lynch, Nicholas J.; Khatri, Priyanka; Bamigbola, Ifeoluwa E.; Chan, Andrew C. Y.; Yabuki, Munehisa; Demopulos, Gregory A.; Heeney, Jonathan L.; Pai, Sumita; Baxendale, Helen; Schwaeble, Wilhelm J. (Frontiers in Immunology, 2022)
A high incidence of secondary Klebsiella pneumoniae and Staphylococcus aureus infection were observed in patients with severe COVID-19. The cause of this predisposition to infection is unclear. Our data demonstrate consumption of complement in acute COVID-19 patients reflected by low levels of C3, C4, and loss of haemolytic activity. Given that the elimination of Gram-negative bacteria depends in part on complement-mediated lysis, we hypothesised that secondary hypocomplementaemia is rendering the antibody-dependent classical pathway activation inactive and compromises serum bactericidal activity (SBA). 217 patients with severe COVID-19 were studied. 142 patients suffered secondary bacterial infections. Klebsiella species were the most common Gram-negative organism, found in 58 patients while S. aureus was the dominant Gram-positive organism found in 22 patients. Hypocomplementaemia was observed in patients with acute severe COVID-19, but not in convalescent survivors three months after discharge. Sera from patients with acute COVID-19 were unable to opsonise either K. pneumoniae or S. aureus and had impaired complement-mediated killing of Klebsiella. We conclude that hyperactivation of complement during acute COVID-19 leads to secondary hypocomplementaemia and predisposes to opportunistic infections.